Effect of Sling Exercise Therapy on Lumbar Function of Patients with Chronic Nonspecific Low Back Pain - CHEN Zhenhua; ZHENG Qikai; CHEN Shuijin; LIN Zhigang (康复学报)
ObjectiveTo observe the effect of sling exercise therapy (SET) on lumbar function of patients with chronic nonspecific low back pain (CNLBP).MethodsA total of 90 patients with CNLBP in the outpatient department of the Affiliated Rehabilitation Hospital of Fujian University of Traditional Chinese Medicine, were divided randomly into conventional Tuina group, exercise training group, and sling exercise group, with 30 cases in each group. The conventional Tuina group received conventional Tuina techniques for lumbar diseases; the exercise training group received the crouching tiger rushing movement in the Yijinjing exercise; the sling exercise group received SET, and the main exercise type was prone bridging training. The treatment time was 15 minutes a time, once a day, for a total of 10 days in three groups. Before and after treatment, the spinal testing and evaluation system was used to measure the maximum strength of psoas muscle flexion and extension; the root mean square (RMS) value of surface electromyography was used to evaluate the muscle activation level of transverse abdominis and multifidus from sitting to standing positions; Roland-Morris disability questionnaire (RMDQ) and Oswestry disability index (ODI) were used to assess the lumbar function.ResultsCompared with that before treatment, the maximum strength of psoas muscle flexion and extension, the RMS value of the transversus abdominis and multifidus from sitting to standing in the three groups increased significantly after treatment, the RMDQ and ODI scores decreased significantly, and the differences were statistically significant (P<0.05). Compared with the conventional Tuina group, the maximum strength of psoas muscle flexion and extension, the RMS value of the transversus abdominis and multifidus from sitting to standing of the exercise training group and the suspension exercise group increased significantly after treatment, the RMDQ and ODI scores decreased significantly, and the differences were statistically significant (P<0.05). Compared with the exercise training group, the maximum strength of psoas muscle flexion and extension, the RMS value of the transversus abdominis and multifidus from sitting to standing of the sling exercise group increased significantly after treatment, the RMDQ and ODI scores decreased significantly, and the differences were statistically significant (P<0.05).ConclusionSET can effectively improve the lumbar and abdominal muscle strength of CNLBP patients, enhance the core stability of the lumbar spine, and improve the lumbar function and activities of daily living, which is recommended for clinical application.